2019
DOI: 10.1155/2019/1321287
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Expression Pattern of SERPINA1 Gene from Duck (Anas platyrhynchos)

Abstract: SERPINA1 is a member of serine protease inhibitors and is increasingly considered to be a regulator of innate immunity in human and animals. However, the expression and function of SERPINA1 gene in immune defense against viral infection remain unknown in ducks. The full-length du SERPINA1 cDNA sequence was obtained using reverse transcription polymerase chain reaction (RT-PCR) and rapid amplification of cDNA ends (RACE). It contained 1457 nucleotide, including 47-bp 5’ UTR, 135-bp 3’ UTR, and 1275-bp open read… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Quantitative analysis showed that only four genes (SPP1, SERPINA1, CLU and CST3) were drastically increased in renal tubules of FGSG patients, consistent with our bioinformatic analysis with transcriptomic data. It was reported that SPP1 [ 36 , 45 , 46 ], APOE [ 47 , 48 , 49 , 50 ], SERPINA1 [ 51 , 52 , 53 ] and CLU [ 54 , 55 , 56 ] were mainly involved in innate immunity, critical for the development of FSGS [ 11 , 57 , 58 , 59 , 60 , 61 , 62 ] especially for the pathogenesnesis of tubular injury [ 63 ]. Innate immunity helps “arrest” circulating monocytes in the pathological sites [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative analysis showed that only four genes (SPP1, SERPINA1, CLU and CST3) were drastically increased in renal tubules of FGSG patients, consistent with our bioinformatic analysis with transcriptomic data. It was reported that SPP1 [ 36 , 45 , 46 ], APOE [ 47 , 48 , 49 , 50 ], SERPINA1 [ 51 , 52 , 53 ] and CLU [ 54 , 55 , 56 ] were mainly involved in innate immunity, critical for the development of FSGS [ 11 , 57 , 58 , 59 , 60 , 61 , 62 ] especially for the pathogenesnesis of tubular injury [ 63 ]. Innate immunity helps “arrest” circulating monocytes in the pathological sites [ 64 ].…”
Section: Discussionmentioning
confidence: 99%